Risk Analysis of Temporary Storage of B3 Waste at PT. PLN (Persero) Main Unit of Transmission in Eastern Java and Bali to the Environment with the Method Failure Mode and Effect Analysis (FMEA) - Sari, Asti Meilinda; Ayu Murti , Restu Hikmah (UPN Veteran Jatim, 2025)
The type of waste that is classified as hazardous and toxic (B3) has characteristics that can cause environmental damage if its management is not carried out safely and according to procedures. The temporary storage facility for B3 waste owned by PT PLN (Persero) East Java and Bali Transmission Main Unit needs special attention so as not to create environmental risks around it. This study aims to identify and assess potential risks in the B3 waste storage area in the company through the FMEA (Failure Mode and Effect Analysis) method. The FMEA method is used to determine the possible failures that can occur in the B3 waste storage system and evaluate the impact it has on the environment. The results of the analysis showed that some failures, such as storage container leaks and ventilation system damage, have a high potential risk associated with soil and water pollution. This risk assessment provides recommendations for improving and strengthening B3 waste management, including improving monitoring and maintenance procedures of storage facilities, as well as improving training for staff involved in waste management. It is hoped that with the implementation of the results of this analysis, it can reduce the potential risks and environmental impacts caused by B3 waste management at PT. PLN (Persero) Main Unit of Transmission in East Java and Bali.